Fine structure of amylopectin and relation with physicochemical properties of three coloured potato starches. (18th August 2020) - Liping, Yang; Xu, Li; Wei, Dongmei; Du, Chuanlai; Yang, Jianting; Zhou, Yibin
Summary: In this study, yellow, red and purple potato starches were selected as the research objects to analyse the fine structure and the relation to the physicochemical properties. Enzymatic hydrolysis and high‐performance anion‐exchange chromatograph were employed to characterise the structure of clusters and φ, β‐limit dextrins. The average degree of polymerisation of clusters from the yellow potato starch was larger (188.57) than in red (91.31) and purple (107.32) potato starch. The molar percentage of fingerprint B chains in yellow, red and purple potato amylopectin were 58.01%, 63.60% and 60.78%, respectively, while major part of short B chains were 15.92%, 17.16% and 16.49%, respectively. The yellow potato amylopectin showed the highest density of branches values indicated that it was more tightly branched. The Pearson correlation coefficients results indicated that the fine structure of amylopectin had significant effects on the physicochemical properties of potato starches, and we can better understanding the differences of the properties among the three potato starches by studying the amylopectin fine structure. Abstract : In this study, starches were isolated from yellow, red and purple potato to analyze the fine structure and the relation to the physicochemical properties. We selected the n‐butyl alcohol and isoamyl alcohol to separate and purify the amylopectin. And in order to study the fine structure of the amylopectin from coloured potato starch, the endo‐enzyme (α‐amylase) was used to prepare cluster, and exo‐enzyme (phosphorylase a and β‐amylase) was used to prepare φ, β‐limit dextrins. By analyzing the correlation between the structure of fine structure and physicochemical properties of starch, aimed to provide information for better understanding the differences of the properties among the three potato starches, and explain the effect of amylopectin fine structure on the functional properties of starch.